Regeneration and thermal stress modification in fiber bragg grating using Co2 laser annealing technique / Lai Man Hong - Lai, Man Hong (2017)
Regenerated fiber Bragg grating (RFBG) is a temperature-resistant grating fabricated from a standard fiber Bragg grating using high temperature annealing treatment. It is well known for its economic production and high temperature sustainability in which the operating temperature of the developed RFBG can be as high as the maximum annealing temperature. It is believed that stress relaxation is one of the contributing factors to the thermal regeneration process. Exploiting the benefits of CO2 laser in terms of dynamic temperature control and focused heating zone, thermal regeneration of RFBG based on CO2 laser annealing has been successfully demonstrated for the first time. The ensuing cooling process after the post-fabrication annealing treatment is the controlling parameter for the modification of thermal stress in the fiber. After an isothermal annealing treatment followed by a slow cooling process, the Bragg wavelength of the RFBG was red-shifted. This modification is reversible by repeating the annealing treatment followed by a rapid cooling process. It is repeatable with different cooling processes in the subsequent annealing treatments. This phenomenon can be attributed to the thermal stress modification in the fiber core by means of manipulation of glass transition temperature with different cooling rates. This finding is important for accurate temperature measurement of RFBG in dynamic environment. Furthermore, the thermal stress relaxation study was extended to birefringence modification in regenerated grating in polarisation maintaining fiber (RGPMF) by using a CO2 laser annealing technique. After conducting a post-fabrication isothermal annealing procedure followed by a slow cooling process, the birefringence of the RGPMF has been increased. This phenomenon can be explained by the changes in the thermal expansion coefficient and glass transition temperature of the stress applying part at different cooling rates. The birefringence modification is reversible by re-annealing with a subsequent rapid cooling process. This finding is useful for the study of the birefringence modification, operation range, sensitivity, and accuracy of PMF or PMF-related fiber components. The finding of this thesis has opened up a new avenue of research on the application of CO2 laser annealing in thermal regeneration, stress relaxation and birefringence modification in FBG components.